2014
DOI: 10.1186/1472-6882-14-58
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo antifungal activities of selected Cameroonian dietary spices

Abstract: BackgroundSpices and herbs have been used in food since ancient times to give taste and flavor and also as food preservatives and disease remedies. In Cameroon, the use of spices and other aromatic plants as food flavoring is an integral part of dietary behavior, but relatively little is known about their antifungal potential.The present work was designed to assess the antifungal properties of extracts from spices used in Cameroonian dietary.MethodsThe in vitro antifungal activities of twenty three extracts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Indeed, essential oils from medicinal spices and vegetables are important sources of antimicrobial agents in addition to their ability to stimulate the digestive system (Rahman et al, 2011). Medicinal spices and vegetables have traditionally been used as food additives, coloring, flavoring and preservative agents as well as antiparasitic, antihelmintic, analgesic, expectorant, sedative, antiseptic and antidiabetic substances in many parts of the world (Rahman et al, 2011;Dzoyem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, essential oils from medicinal spices and vegetables are important sources of antimicrobial agents in addition to their ability to stimulate the digestive system (Rahman et al, 2011). Medicinal spices and vegetables have traditionally been used as food additives, coloring, flavoring and preservative agents as well as antiparasitic, antihelmintic, analgesic, expectorant, sedative, antiseptic and antidiabetic substances in many parts of the world (Rahman et al, 2011;Dzoyem et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Spices and herbs have been used in African countries since ancient times not only to give taste and flavour to foods but also as food preservatives and to prevent and cure diseases (Dzoyem et al 2014). This aspect has recently attracted the attention of many scientists and encouraged them to conduct screening for biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…giganteus, belonging to the Asteraceae family, is a branched herb, 60-150 cm tall, with roots that are widely used in the traditional medicine of Cameroon and Nigeria for the treatment of various diseases and illnesses such as heart and gastric troubles, to calm stomach ache, to give carminative help and reduce the effects of alcohol, and reduces asthma attacks (Menut et al 1997;Tene et al 2004). In previous studies, the methanolic extract of this plant has been shown to have antibacterial , antifungal (Dzoyem et al 2014) and antioxidant effects (Abdou et al 2010). The cytotoxicity of crude methanol extract of roots has also been demonstrated Kuete et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and in vitro experiments have indicated that the Beilschmiedia plant extracts possess a variety of pharmacological aspects with antioxidant, anti-inflammatory, cytotoxicity, antibacterial and antifungal activities [23][24][25][26]. With consideration of the importance of the therapeutic property of this genus to heal various ailments.…”
Section: Introductionmentioning
confidence: 99%